2009
DOI: 10.3168/jds.2008-1199
|View full text |Cite
|
Sign up to set email alerts
|

Nongenetic effects and genetic parameters for length of productive life of Holstein cows in Hokkaido, Japan

Abstract: Records of Holstein dairy cows in Hokkaido, Japan, were used to study the effects of environmental factors on length of productive life and to estimate genetic parameters for length of productive life. Each record was assigned to 1 of 3 data sets depending on the percentage of type-scored cows in the herd. This percentage was considered to partly reflect the management policy in each herd, in particular regarding culling. The A, B, and C data sets consisted of herds with none, less than 60%, and more than 60% … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
26
0
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(37 citation statements)
references
References 15 publications
8
26
0
3
Order By: Relevance
“…Previous studies have shown that the hazard value during early DIM in each parity was as low as 0.0003 to 0.0005, and increased from 250 to 280 DIM (Ducrocq, 2002(Ducrocq, , 2005Terawaki and Ducrocq, 2009). Similarly, previous studies have revealed that the plot of {ln[− ln(survival function)]} typically shows a mostly linear increase up to 150 DIM, with a more rapid increase thereafter (Roxström et al, 2003;Holtsmark et al, 2009).…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…Previous studies have shown that the hazard value during early DIM in each parity was as low as 0.0003 to 0.0005, and increased from 250 to 280 DIM (Ducrocq, 2002(Ducrocq, , 2005Terawaki and Ducrocq, 2009). Similarly, previous studies have revealed that the plot of {ln[− ln(survival function)]} typically shows a mostly linear increase up to 150 DIM, with a more rapid increase thereafter (Roxström et al, 2003;Holtsmark et al, 2009).…”
Section: Discussionmentioning
confidence: 87%
“…Terawaki and Ducrocq (2009) reported that the ˆ, h s eff 2 obtained using a piecewise Weibull baseline in Holsteins in the Hokkaido region of Japan ranged from 0.046 to 0.134. Moreover, Sasaki et al (2012) reported that the ˆ, h s eff 2 obtained using a unique Weibull baseline in Holsteins in Japan ranged from 0.101 to 0.105.…”
Section: Strmmentioning
confidence: 99%
“…Comparing culling risks between lactations, the lowest hazard was found in the first lactation, as in French Holstein (Ducrocq, 2005) and Japanese Holstein cattle (Terawaki et al, 2006;Terawaki and Ducrocq, 2009) using a similar approach. The differences between shape parameters were small for the third and fourth stages, and the two stages could have been merged; however, as the number of records was large enough, five different lactation stages were retained.…”
Section: Discussionmentioning
confidence: 99%
“…With a high level of involuntary culling, a farmer has less opportunity to cull low-producing cows voluntarily. In the past, voluntary culling was assumed to be mainly for milk yield, and there is evidence that low-producing cows are more likely to be culled than high-producing cows (Vollema et al, 2000;Sewalem et al, 2005;Terawaki and Ducrocq, 2009). However, in expanding herds in Wisconsin, for low-producing cows the relative risk for culling decreased during the period 1981-2000, whereas the relative risk increased for high-producing cows (Weigel et al, 2003).…”
Section: Introductionmentioning
confidence: 99%